Silent Eloquence : Lucian and Pantomime Dancing. - Lada-Richards, Ismene (Classical literature and society., 2013)
One of the greatest aesthetic attractions in the ancient world was pantomime dancing, a ballet-style entertainment in which a silent, solo dancer incarnated a series of mythological characters to the accompaniment of music and sung narrative. Looking at a multitude of texts and particularly Lucian's ""On the Dance"", a dialogue written at the height of pantomime's popularity, this innovative cultural study of the genre offers a radical reassessment of its importance in the symbolic economy of imperial and later antiquity. Rather than being trivial or lowbrow, pantomime was thoroughly enmeshed